Pengaruh Literasi Lingkungan terhadap Environmental Responsibility Siswa di SMA Negeri Kebakkramat Kabupaten Karanganyar - Hamidah, Afifah Nur; Dewi, Ratih Puspita (Universitas Pendidikan Ganesha, 2025)
Environmental literacy is an important aspect in shaping students' understanding and attitudes toward environmental issues. Although efforts to improve environmental literacy have been made, there has been limited research on its impact on students' environmental responsibility attitudes. Therefore, further research is needed to examine the role of environmental literacy in shaping students' responsibility toward environmental conservation. This study aims to analyze the environmental literacy of students at SMA Negeri Kebakkramat, the environmental responsibility of students at SMA Negeri Kebakkramat, and the effect of environmental literacy on students' environmental responsibility at SMA Negeri Kebakkramat. This research uses a quantitative method with a correlational design, with 136 respondents who are eleventh-grade students. Data collection techniques in this study include tests, questionnaires, and documentation, with data analysis using the bivariate Pearson correlation test. The results of the study show that the environmental literacy of students at SMA Negeri Kebakkramat has an average score of 17.6, which falls into the medium category. The environmental responsibility of students at SMA Negeri Kebakkramat has an average score of 75.7, which also falls into the medium category. There is a significant influence (sig. 0.000 < 0.05) between environmental literacy and students' environmental responsibility at SMA Negeri Kebakkramat.